Riskienhallinnan ajankohtaisia teemoja - Havakka, Pauliina; Kulmala, Jarna; Koskinen, Lasse; Ahteensivu, Aarno (Tampere University Press, 2018)
This book presents a variety of different themes related to risks and risk management. The book consists of research papers aimed at supplementing and updating the topics discussed previously in risk management literature. The articles cover the key concepts and essence of risk and risk management, basic issues of security construction, risk awareness in corporate decision-making, reputation risk and its impact on business operations, social risks, their significance and the dimensions of social risk management. The last article presents the freely available RiskDemo software, which allows the reader to test and illustrate a wide range of risk features. The book aims to respond to the recent changes in the risk management environment as well as to stimulate academic debate on the subject.